Disease, Cataclysm, or Industrialisation? A Comment on the Existence and Disappearance of a Modern Period Settlement in the Vicinity of Trachy in Upper Silesia - Radosław Zdaniewicz; Henryk Postawka (Fasciculi Archaeologiae Historicae, 2021)
An analysis of map charts of Upper Silesia from the second half of the 18th century allows us to identify at least a few lost settlements and hamlets. There is no doubt that one such lost settlement existed upon the Bierawka river, in the vicinity of the present-day villages of Trachy (Althammer) and Tworóg Mały (Quarghammer). Regrettably, the exact location of this settlement has never been identified. An archival query and test excavations demonstrated that the settlement actually came into existence and developed as late as the Modern Period. A fragment of a stone and brick foundation that was uncovered in the course of excavations was the vestige of a hut or of a more professional industrial workshop, such as a finery or forge. It was equipped with a waterwheel. Unfortunately, the reasons behind the disappearance of the village are unknown. It may have been caused by one of the epidemics which affected the inhabitants of Upper Silesia in the 19th century or by another cataclysm. It cannot be excluded, however, that the disappearance may have been due to the economic transformations of the 19th century.